2016
DOI: 10.1177/0969733016654318
|View full text |Cite
|
Sign up to set email alerts
|

Threats to nurses’ dignity and intent to leave the profession

Abstract: According to the views of nurses themselves, identification of the factors threatening nurses' dignity can be one of the appropriate solutions for the broader and deeper investigation of this phenomenon and can help promote and support nurses' dignity and their retention within the profession.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 32 publications
0
35
0
1
Order By: Relevance
“…The participants’ perceived support from relatives or friends was higher than support from coworkers and supervisors in this study. This might be because with increasing nursing shortages and financial restrictions, obtaining support from coworkers may be impractical (Valizadeh et al., ). All sources of support had significantly positive bivariate correlations with the physical and mental health of nurses, which is consistent with previous studies (Sun et al., ; Weigl et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The participants’ perceived support from relatives or friends was higher than support from coworkers and supervisors in this study. This might be because with increasing nursing shortages and financial restrictions, obtaining support from coworkers may be impractical (Valizadeh et al., ). All sources of support had significantly positive bivariate correlations with the physical and mental health of nurses, which is consistent with previous studies (Sun et al., ; Weigl et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Nurse participants from two teaching hospitals in Iran revealed in a qualitative study that an overemphasis of their service‐giving nature by hospital management threatened their professional dignity. Disrespect from their medical colleagues and an oppressive work environment strengthened their intent to leave the profession (Valizadeh et al 2018). In the same country, Najafi et al (2017) involved professional nurses from public and private hospitals to explore the threats to nurses’ dignity and professional reputation.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of previous studies indicated that the dominance of physicians obstructed the provision of treatment and care by nurses [19,38]. In another study, professional autonomy was defined as independent but collaborative functioning in a complex clinical setting [13].…”
Section: Discussionmentioning
confidence: 99%
“…Professional autonomy has become a prerequisite for nurses due to their wide range of functions and responsibilities [13,15]. On the other hand, excessive strain on nurses, due to work-related issues, has resulted in anxiety, job dissatisfaction, and the intention to change jobs [19]. Respect and professional autonomy are the main demands of nurses worldwide [12].…”
Section: Introductionmentioning
confidence: 99%